Business driven information systems - Baltzan, Paige (New York : McGraw-Hill, 2023)
'Business Driven Information Systems discusses various business initiatives first and how technology supports those initiatives second. The premise for this unique approach is that business initiatives should drive technology choices. Every discussion first addresses the business needs and then addresses the technology that supports those needs. This text provides the foundation that will enable students to achieve excellence in business, whether they major in operations management, manufacturing, sales, marketing, finance, human resources, accounting, or virtually any other business discipline. Business Driven Information Systems is designed to give students the ability to understand how information technology can be a point of strength for an organization'--
Includes bibliographical references and index.
Buku bacaan asas Fakulti Ekonomi dan Pengurusan.
Keywords: Information technology -- Management; Industrial management -- Data processing